Economic and Social Sustainability - Regina T. Riphahn; Klaus M. Schmidt (Wirtschaftsdienst)
Abstract The scientific advisory board of the federal ministry of economic affairs and climate protection conducted a symposium on sustainability at its 500th meeting. The UN’s sustainable development goals play an increasingly important role in economic policy and regulation. This article gives a survey of the trade-offs and implementation problems that were discussed at the symposium, in particular the operationalisation of sustainability in welfare economics, the implementation of sustainability goals in economic law, the relationship between competition policy and sustainability, the impact of sustainability concerns on monetary policy, and finally, supply chain regulation and sustainability objectives.